The big law enforcement information exchange challenge (Belügyi Szemle, 2024)
Aim: The paper attempts to take stock and present the most significant dilemmas and challenges of cross border criminal data and intelligence exchange between law enforcement authorities of EU Member States that can be experienced by police personnel in the field at the moment.Methodology: In addition to the relevant legislation, recommendations and best practices, the paper – based on personal experience as a police professional, supplemented by insights of the members of the EU law enforcement community – describes and illustrates the various challenges of today’s international police cooperation landscape.Findings: The EU law enforcement information exchange scene is in the midst of its transformation due to globalisation and the progressive information and communication technology advancement. The evolution of the institutionalised cross border criminal data and intelligence exchange has to keep up with the world of crime and reflect the challenges which arise from the sensitive nature of the policy area itself, where any substantial development can only be reached by innovation and capacity building of the law enforcement sector.Value: This snapshot is to give a structured overview and to draw more attention to the complexity and the controversies of the international law enforcement information exchange landscape, which policy-makers and police professionals have to face nowadays in order to successfully prevent, detect or investigate cross border criminal offences.